2011
DOI: 10.1177/0022034510393517
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Replacement Therapy Prevents Dental Defects in a Model of Hypophosphatasia

Abstract: Hypophosphatasia (HPP) occurs from loss-of-function mutation in the tissue-non-specific alkaline phosphatase (TNALP) gene, resulting in extracellular pyrophosphate accumulation that inhibits skeletal and dental mineralization. TNALP-null mice (Akp2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
105
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 33 publications
12
105
0
1
Order By: Relevance
“…Local TNAP deficiency (by IHC), hypophosphatemia, and hypocalcemia were ruled out as causes of cementum inhibition in Bsp -/-mice. It is notable that acellular cementum formation is similarly inhibited in the Alpl -/-mouse model featuring loss of TNAP function (Beertsen et al, 1999;McKee et al, 2011;Foster et al, 2012). Alpl -/-mice harbor increased levels of the mineral inhibitor pyrophosphate (PP i ) and serve as a model of hypophosphatasia (HPP), where lack of acellular cementum predisposes to tooth loss (van den Bos et al, 2005).…”
Section: Acellular Cementum As a Mineralization-sensitive Tissuementioning
confidence: 99%
“…Local TNAP deficiency (by IHC), hypophosphatemia, and hypocalcemia were ruled out as causes of cementum inhibition in Bsp -/-mice. It is notable that acellular cementum formation is similarly inhibited in the Alpl -/-mouse model featuring loss of TNAP function (Beertsen et al, 1999;McKee et al, 2011;Foster et al, 2012). Alpl -/-mice harbor increased levels of the mineral inhibitor pyrophosphate (PP i ) and serve as a model of hypophosphatasia (HPP), where lack of acellular cementum predisposes to tooth loss (van den Bos et al, 2005).…”
Section: Acellular Cementum As a Mineralization-sensitive Tissuementioning
confidence: 99%
“…24 In Tnsalp knockout mice, which constitute an animal model of infantile hypophosphatasia, 25 treatment with daily subcutaneous injections of ENB-0040 at doses that result in serum levels ranging from 650 to 1000 U per liter preserve the mineralization of bones and teeth. 24,26,27 A phase 1 study involving adult patients with hypophosphatasia showed peak and trough ENB-0040 levels in this range after one intravenous dose of 3 mg per kilogram of body weight and weekly subcutaneous doses of 2 mg per kilogram. 28 We conducted a clinical trial of treatment with ENB-0040 for at least 1 year in infants and young children with life-threatening hypophosphatasia.…”
mentioning
confidence: 99%
“…Defects in cementum, dentin, alveolar bone, and enamel have been demonstrated in Alpl -/-mice (McKee et al 2011;Foster et al 2012;Yadav et al 2012;Foster, Nagatomo, et al 2013;Zweifler et al 2015). However, these mice die by 2 to 3 wk of age, thereby preventing analysis of HPP-associated pathologies at advanced ages.…”
mentioning
confidence: 99%